The effectiveness of RA approach on rat among primary school students - Rathakrishnan, Mohan (2015)
Reading is one of the main literacy skills for second or foreign language learners to obtain knowledge.However one must not only be able to read, but one must also have good reading habits.Educators are confronted with a constant struggle to motivate students to learn in all content areas, including reading.This study concentrates on an investigation of the effects of reading aloud on students‟ reading performance particularly in English context.Acknowledging the importance of reading, this paper attempts to demonstrate that effect of Reading Aloud approach on students Reading Attitude (RA-RAT) is a viable method to improve students‟ English reading habits at initial stage.This study examined 80 Year 5 students‟ reading preferences and their responses towards the program as two criteria.A posttest: School Based Oral Assessment (SBOA), questionnaire, observation and interview were used for collecting data.The results indicated that there is effectiveness of reading aloud approach on the overall students‟ reading achievement, students‟ reading ability, as well as students‟ attitude towards reading aloud approach.The finding also shows there is significant difference in overall reading performance between male students in the experimental group who had participated in a reading aloud activity as compared to male students in the control group